2014
DOI: 10.1155/2014/838627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blade Outlet Angle on Unsteady Hydrodynamic Force of Closed-Type Centrifugal Pump with Single Blade

Abstract: Geometrically, the single-blade centrifugal impeller, commonly used today as a sewage pump, is not axially symmetric. For this reason, the static pressure around the impeller fluctuates greatly when the impeller is rotating, and not only the radial thrust but also the axial thrust shows large fluctuations. Therefore, it is extremely important for the improvement of pump reliability to quantitatively grasp these fluctuating hydrodynamic forces. In this study, we investigated the unsteady hydrodynamic forces in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Previous studies have confirmed that the clearance flow in the sidewall gaps, sensitive to the clearance size, is able to influence the pump performance (Engeda, 1995; Shukla and Kshirsagar, 2007; Li, 2012; Wu et al , 2014; Cao et al , 2015). Moreover, experiments and simulations also indicate that the clearance flow contributes substantially to the rotordynamic forces, especially the radial force and axial thrust on the impeller (Adkins and Brennen, 1988; Uy and Brennen, 1999; Park and Morrison, 2009; Will et al , 2012; Nishi and Fukutomi, 2014; Liu et al , 2014). The above clearance flow effect is derived from the interaction between the clearance flow in the sidewall gap and the main flow in the volute casing and impeller.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed that the clearance flow in the sidewall gaps, sensitive to the clearance size, is able to influence the pump performance (Engeda, 1995; Shukla and Kshirsagar, 2007; Li, 2012; Wu et al , 2014; Cao et al , 2015). Moreover, experiments and simulations also indicate that the clearance flow contributes substantially to the rotordynamic forces, especially the radial force and axial thrust on the impeller (Adkins and Brennen, 1988; Uy and Brennen, 1999; Park and Morrison, 2009; Will et al , 2012; Nishi and Fukutomi, 2014; Liu et al , 2014). The above clearance flow effect is derived from the interaction between the clearance flow in the sidewall gap and the main flow in the volute casing and impeller.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-stage pump is composed of multiple single-stage impellers, and the research results on axial forces in single-stage pumps can be used as a reference for multi-stage pumps. Nishi and Fukutomi 16 studied the effect of the change in outlet placement angle of single-vane closed centrifugal pumps on axial forces, and the result shows that at large flow rates, the time average value of the axial forces in the front and rear pump chamber increased with the increase of impeller vane outlet angle. Kazakov and Pelinskii 17 carried out an experimental study on axial force of submersible well pump, it was found that the pump axial force increased with the seal gap increased.…”
Section: Introductionmentioning
confidence: 99%
“…Aoki [3] measured the transient pressure distribution on the impeller blade of an open single-blade centrifugal and obtained the impeller's dynamic and static radial force. Nishi [4] studied the radial force of a single blade centrifugal pump by a numerical simulation and experiment, analyzed the influence of the blade outlet angle and blade outlet width on the radial force, and found that increasing the blade outlet width can reduce the mean value of radial force under small flow conditions. Meng [5] and Al [6] studied the radial force of a centrifugal pump with guide vanes and found that the asymmetry of pressure in each flow channel of the impeller was the main reason for the radial force of the impeller.…”
Section: Introductionmentioning
confidence: 99%